1999
DOI: 10.1007/s004270050296
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical study on the triple origin of the sphincter iris in the chick embryo

Abstract: The ontogenic development of the sphincter iris has been studied by immunocytochemistry and standard staining on chick embryos from stage 25 HH to the time of hatching. We have used the monoclonal antibody 13F4, a highly specific marker of muscular cells. We have observed three different regions in the iris. In the pupillary region, immunoreactive cells are in continuous contact with the inner epithelium of the pupillary margin. In the intermediate region, the outer epithelium forms buds of pigmented cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…5 A-C). These cells therefore were not derived from the pigmented OV epithelium, as previously proposed by Barrio-Asensio and coworkers (Barrio-Asensio et al, 1999;Barrio-Asensio et al, 2002). …”
Section: Neural Crest Derivatives In Intra-and Peri-ocular Structuressupporting
confidence: 59%
“…5 A-C). These cells therefore were not derived from the pigmented OV epithelium, as previously proposed by Barrio-Asensio and coworkers (Barrio-Asensio et al, 1999;Barrio-Asensio et al, 2002). …”
Section: Neural Crest Derivatives In Intra-and Peri-ocular Structuressupporting
confidence: 59%
“…7E and 7F), even though the similar staining intensity remained in the residual Pax6-positive iris stromal cells. Furthermore, a muscle-specific marker (monoclonal antibody 13F4) (Rong et al, 1987;Barrio-Asensio et al, 1999) also revealed abnormal iris muscle organization in Six3 virus-infected eyes compared with the control virus-infected eye (Figs. 7G and 7H).…”
Section: Effects Of Six3 Misexpression On Molecular Markers Of the Pementioning
confidence: 93%
“…2E and 2F). The anti-Pax6 (Ericson et al, 1997), anti-type IX collagen (2C2; Irwin et al, 1985;Fitch et al, 1988), anti-keratan sulfate (I22;Funderbergh et al, 1982Funderbergh et al, , 1986, anti-muscle cell specific antigen (13F4; Rong et al, 1987;Barrio-Asensio et al, 1999), and the anti-viral GAG protein (3C2; Stoker and Bissell, 1987) monoclonal antibodies were obtained from the Developmental Studies Hybrid-oma Bank (DSHB, Iowa City). The polyclonal antibodies p27 against the viral GAG protein were purchased from SPAFAS.…”
Section: Immunocytochemistry and Quantificationmentioning
confidence: 99%
“…Classically, the iris muscles are described as unstriated in mammals, fish, and amphibia, but striated in birds and reptiles. However, both pharmacological and histological work suggests the irises of some reptiles (Iske, 1929;Reger, 1966) and many birds in fact contain both striated and non-striated muscle components (Gabella & Clarke, 1983;Yamashita & Sohal, 1986;Scapolo et al, 1988;Barrio-Asensio et al, 1999;Loerzel et al, 2002). Although the non-striated tissue can be located throughout the iris in smooth muscle cells within the stroma, it often forms a distinct myoepithelial dilator muscle (Walls 1942 for review of earlier literature; van Oehme, 1969;Nishida & Sears, 1970;Oliphant et al, 1983;Dieterich et al, 1988).…”
Section: Iris Structurementioning
confidence: 99%